2019
DOI: 10.1136/archdischild-2019-317245
|View full text |Cite
|
Sign up to set email alerts
|

Symptom interval and treatment burden for patients with malignant central nervous system germ cell tumours

Abstract: ObjectivePatients with central nervous system germ cell tumours (CNS-GCTs) commonly initially present to primary care or general paediatricians. Prolonged symptom intervals (SI) are frequently seen in CNS-GCTs and have been associated with inferior outcomes in other brain tumours. This study reviewed the clinical presentation of CNS-GCTs and examined the effect of prolonged SI.Design/Setting/Patients/OutcomesInternational multicentre 10-year retrospective study (2002–2011 inclusive), across six international p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 27 publications
4
33
1
Order By: Relevance
“…No correlation between diagnostic delay and metastatic disease were found, differently from previous studies 17,23 . While Phi et al 20 reported a significant association of deferred diagnosis with a poorer outcome in a subset of germinoma cases (n=13) among a cohort of 181 patients with localised IC-GCT, this result was not seen in other single-centre studies 15,17 nor in our multicentre study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…No correlation between diagnostic delay and metastatic disease were found, differently from previous studies 17,23 . While Phi et al 20 reported a significant association of deferred diagnosis with a poorer outcome in a subset of germinoma cases (n=13) among a cohort of 181 patients with localised IC-GCT, this result was not seen in other single-centre studies 15,17 nor in our multicentre study.…”
Section: Discussioncontrasting
confidence: 99%
“…The median time to diagnosis of IC-GCT in our cohort was 4 months, shorter than the Japanese report 21 . Nevertheless, we have shown that the interval from the first symptom to diagnosis may vary significantly and, in some cases, may extend to nearly 5 years, confirming the wide variation already reported 17,18,23 . DI was often an early clinical manifestation in our cohort (70.6% of subjects who displayed endocrinopathy as first symptom), as described in other studies 18,19,30 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Patients presenting endocrinological symptoms had a significant delay in diagnosis [ 39 ]. Approximately one-third of the patients have prolonged symptomatology (>6 months) before the diagnosis, these cases being associated with a higher risk of metastatic disease [ 46 ]. A summary of the clinical presentation is shown in Table 1 .…”
Section: Clinical Presentationmentioning
confidence: 99%
“… 1 , 2 Intracranial GCTs are difficult to be differentiated from various neoplastic or inflammatory diseases due to similar clinical, radiological, and even pathological findings. 3 - 5 …”
mentioning
confidence: 99%